2013
DOI: 10.1080/13691058.2013.774050
|View full text |Cite
|
Sign up to set email alerts
|

The eroticism of Internet cruising as a self-contained behaviour: a multivariate analysis of men seeking men demographics and getting off online

Abstract: Most studies on men seeking men and who use the Internet for sexual purposes have focused on the epidemiological outcomes of Internet cruising. Other research has only focused on online sexual behaviours such as cybersex. The present study examines men who find the acts of Internet cruising and emailing to be erotic as self-contained behaviours. We surveyed 499 men who used craigslist.org for sexually-oriented purposes, and ran an ordinary least squares multiple regression model to determine the demographic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…This is especially true for research on the sexual risk behaviors of MSM who have used the internet for partner seeking since the early 1990s [24]. SNS designed for partner-seeking among MSM have grown popular because they give users the ability to (a) conveniently and quickly locate sexual partners [25], (b) sort opportunities for sex by partner characteristics and preferences [26], (c) control information about sexual preferences and behaviors [27], and (d) engage with a community of similar individuals that can provide social support free from stigmatized reactions from friends and family [27-29]. A study of 2,505 MSM from the UK demonstrated that from 1993 to 2002, the percentage of MSM who met their first male sexual partner through the internet increased from 3% to 61% [30]; at the same time percentages of MSM who met their partners in gay venues such as bars and clubs declined from 34% to 17%.…”
Section: Resultsmentioning
confidence: 99%
“…This is especially true for research on the sexual risk behaviors of MSM who have used the internet for partner seeking since the early 1990s [24]. SNS designed for partner-seeking among MSM have grown popular because they give users the ability to (a) conveniently and quickly locate sexual partners [25], (b) sort opportunities for sex by partner characteristics and preferences [26], (c) control information about sexual preferences and behaviors [27], and (d) engage with a community of similar individuals that can provide social support free from stigmatized reactions from friends and family [27-29]. A study of 2,505 MSM from the UK demonstrated that from 1993 to 2002, the percentage of MSM who met their first male sexual partner through the internet increased from 3% to 61% [30]; at the same time percentages of MSM who met their partners in gay venues such as bars and clubs declined from 34% to 17%.…”
Section: Resultsmentioning
confidence: 99%
“…MSM users of e-dating cannot be considered a homogeneous group, but diverse and plural in terms of sexual identity 7 . The results caution against the stereotypes that limit cruising to the self-identified homosexual population and suggest a much more unstable view of gender and sexuality 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The acronym MSM can cause confusion if we accept it as an ontological social category, overlooking its epidemiological genesis in the process. Despite its limitations, the acronym's use in this study helps us de-stigmatize the practices that interest us here (cruising) as exclusive to the gay community, thus responding to studies that point to eroticization via the Internet by men self-identified as bisexual or heterosexual 7 .…”
Section: Background and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…One branch of the literature on attracting and selecting intimate partners focuses on people's self‐presentational strategies to attract potential sexual and romantic partners (Blackwell, Birnholtz, & Abbott, 2015; Ellison, Heino, & Gibbs, 2006; Hobbs, Owen, & Gerber, 2017). The second branch of this literature analyzes how the technological affordances of digital dating platforms structure online intimacies, including dating websites and mobile dating applications (Chan, 2018; Davis, Hart, Bolding, Sherr, & Elford, 2006; Lynch, 2010; Race, 2015; Robinson & Moskowitz, 2013).…”
Section: Intimacy and Online Datingmentioning
confidence: 99%